Analisis Hukum Jaminan Sosial Ketenagakerjaan Bagi Pekerja Migran Indonesia: Komparasi Indonesia dan Belanda - Rangga Yudha Leonspatra; Rafli Ilham Bimantoro; Ahmad Harland Fadhilah (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Social Security for Employment is a form of protection for workers, including those employed domestically and Indonesian migrant workers. The Social Security for Employment program for Indonesian migrant workers covers Work Accident Insurance, Death Insurance, and Old Age Insurance. On the other hand, the Netherlands is one of the countries with the most comprehensive social security systems in Europe. Therefore, this study was written to analyze the regulations governing Social Security for Indonesian Migrant Workers within the national framework and to compare these regulations with those in the Netherlands. This research is a legal-normative study using a statutory approach, a conceptual approach, and a comparative approach. The results of this study indicate that the social security program for Indonesian migrant workers is deemed inadequate by the government in ensuring a decent standard of living for Indonesian migrant workers, as it lacks pension benefits and unemployment insurance. Meanwhile, when compared with the social security system in the Netherlands, Indonesia should consider adopting it, as it is perceived to provide greater protection for migrant workers.